Targeting AKT-Dependent Regulation of Antioxidant Defense Sensitizes AKT-E17K Expressing Cancer Cells to Ionizing Radiation - Goetting, Isabell; Larafa, Safa; Eul, Katharina; Kunin, Mikhail; Jakob, Burkhard; Matschke, Johann; Jendrossek, Verena (Frontiers in Oncology, 2022)
Aberrant activation of the phosphatidyl-inositol-3-kinase/protein kinase B (AKT) pathway has clinical relevance to radiation resistance, but the underlying mechanisms are incompletely understood. Protection against reactive oxygen species (ROS) plays an emerging role in the regulation of cell survival upon irradiation. AKT-dependent signaling participates in the regulation of cellular antioxidant defense. Here, we were interested to explore a yet unknown role of aberrant activation of AKT in regulating antioxidant defense in response to IR and associated radiation resistance. We combined genetic and pharmacologic approaches to study how aberrant activation of AKT impacts cell metabolism, antioxidant defense, and radiosensitivity. Therefore, we used TRAMPC1 (TrC1) prostate cancer cells overexpressing the clinically relevant AKT-variant AKT-E17K with increased AKT activity or wildtype AKT (AKT-WT) and analyzed the consequences of direct AKT inhibition (MK2206) and inhibition of AKT-dependent metabolic enzymes on the levels of cellular ROS, antioxidant capacity, metabolic state, short-term and long-term survival without and with irradiation. TrC1 cells expressing the clinically relevant AKT1-E17K variant were characterized by improved antioxidant defense compared to TrC1 AKT-WT cells and this was associated with increased radiation resistance. The underlying mechanisms involved AKT-dependent direct and indirect regulation of cellular levels of reduced glutathione (GSH). Pharmacologic inhibition of specific AKT-dependent metabolic enzymes supporting defense against oxidative stress, e.g., inhibition of glutathione synthase and glutathione reductase, improved eradication of clonogenic tumor cells, particularly of TrC1 cells overexpressing AKT-E17K. We conclude that improved capacity of TrC1 AKT-E17K cells to balance antioxidant defense with provision of energy and other metabolites upon irradiation compared to TrC1 AKT-WT cells contributes to their increased radiation resistance. Our findings on the importance of glutathione de novo synthesis and glutathione regeneration for radiation resistance of TrC1 AKT-E17K cells offer novel perspectives for improving radiosensitivity in cancer cells with aberrant AKT activity by combining IR with inhibitors targeting AKT-dependent regulation of GSH provision.